Inside Oracle Designer/2000 - Lulushi, Albert (Prentice Hall PTR, 1998)
Master Oracle's Designer/2000 Release 2 with this complete, up-to-date reference and tutorial. Inside Oracle Designer/2000 walks you through every step of business process modeling, software engineering, and implementation with Oracle's breakthrough Designer/2000 suite. You'll start by developing a simple application system that covers all the Designer/2000 and RAD basics you'll need to know, including: * Modeling entities and relationships * Creating function hierarchies * Transforming requirements in database objects and software modules * Maintaining object properties * Generating database objects and software modules Inside Oracle Designer/2000 presents detailed coverage of make-or-break technical issues such as application partitioning and thin-client development. You'll learn to use every component of Designer/2000, design database systems, generate software modules of different flavors, and maintain the systems you create. You'll also get practical guidance with the business side of process reengineering: * Modeling the enterprise's strategic direction and information infrastructure * Preparing for reengineering and continuous process improvement * Creating process models th